2018
DOI: 10.1177/1479164118780799
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and abdominal aortic aneurysms: A review of the mechanisms underlying the negative relationship

Abstract: The negative association between diabetes and abdominal aortic aneurysm is robust. Future studies should attempt to target the pathways identified in this review to develop novel therapeutic agents aimed at slowing or even halting aneurysm progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…Regarding DM in our study, it seemed to have a protective effect for IA formation (6.8% in IA vs. 12.5% in controls; p = 0.001). Dattani et al [51] reported a negative association between AAA and DM. In addition, medications to treat DM can inhibit AAA formation and growth [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding DM in our study, it seemed to have a protective effect for IA formation (6.8% in IA vs. 12.5% in controls; p = 0.001). Dattani et al [51] reported a negative association between AAA and DM. In addition, medications to treat DM can inhibit AAA formation and growth [51].…”
Section: Discussionmentioning
confidence: 99%
“…Dattani et al [51] reported a negative association between AAA and DM. In addition, medications to treat DM can inhibit AAA formation and growth [51]. Therefore, further studies regarding DM and medications on IA formation and growth are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased levels of total cholesterol and apolipoprotein B, both markers easily quantified and major constituents of lipid metabolism, have been associated with increased growth rates of AAA [ 18 ]. On the other hand, given the potentially protective nature of diabetes mellitus in AAA, glycated hemoglobin (HbA1c) has been studied as a possible biomarker of inverse association with AAA expansion [ 52 , 53 , 54 , 55 ]. A lower growth rate was observed in patients with higher HbA1c levels; 1.8 mm/year decrease of rate in HbA1c 44–77 compared to 28–39 mmol/mol [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Hyperglycemia might influence angiogenesis, remodeling, extracellular matrix volume and glycation, advanced glycation end-products, inflammatory markers, oxidative stress, composition of the thrombus commonly present in an AAA, and transforming growth factor b signaling. [23][24][25] Furthermore, hemodynamic features of the aorta might differ between diabetic and nondiabetic patients, and computational fluid dynamic methods are currently evaluated to help understand such mechanisms. 26 Our methodology does not allow us to speculate about these mechanisms, however, as we have not assessed biomarkers.…”
Section: Discussionmentioning
confidence: 99%